2021
DOI: 10.1080/14631377.2020.1867430
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetric effects of fiscal policy on inflation and economic activity in post-communist European countries

Abstract: Fiscal policy plays an important role in stimulating economic activity, but it also has a significant influence in securing monetary stability in an economy. Our study aims to analyse the asymmetric effects of fiscal policy on inflation and economic activity on twelve post-communist European countries that are associated with the European Union (EU) by either membership or by being members of the Eastern European Partnership (EaP). We explore the asymmetric effects on inflation and economic activity by using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Furthermore, the estimate parameter in the short run is significant as shown in Table 4 (see parameter C(4). In a general framework, recent studies confirmed the significance of public expenditure on inflation rates (Asandului et al, 2021), studied a set of post-communist European countries and showed the existence of asymmetric effects of public expenditure (generally fiscal policy) on inflation. In another set of countries, (Nguyen, 2019) analyzed the co-integration between public spending and inflation in China, India and Indonesia, the empirical findings showed a positive effect of public expenditure on inflation in India and Indonesia and a negative effect in China.…”
Section: Effects On the Rate Of Inflationmentioning
confidence: 94%
“…Furthermore, the estimate parameter in the short run is significant as shown in Table 4 (see parameter C(4). In a general framework, recent studies confirmed the significance of public expenditure on inflation rates (Asandului et al, 2021), studied a set of post-communist European countries and showed the existence of asymmetric effects of public expenditure (generally fiscal policy) on inflation. In another set of countries, (Nguyen, 2019) analyzed the co-integration between public spending and inflation in China, India and Indonesia, the empirical findings showed a positive effect of public expenditure on inflation in India and Indonesia and a negative effect in China.…”
Section: Effects On the Rate Of Inflationmentioning
confidence: 94%
“…( Asandului et al, 2021 , Baig et al, 2021 , Behera and Rath, 2021 , Boneva et al, 2018 , Jordà et al, 2015 , Long et al, 2022 , Lovcha and Perez-Laborda, 2018 , Musunuru and Jawed, 2022 , Njindan Iyke et al, 2007 , Prabheesh et al, 2003 , Rabanal and Quint, 2013 , Salisu et al, 2021 , Sharma and Sha, 2020 , Smets, 2018 )…”
Section: Uncited Referencesmentioning
confidence: 99%
“…Furthermore, Sharma and Mittal (2019) provide some evidence about the presence of an asymmetric connection between fiscal deficit and GDP in the short and long run based on the nonlinear ARDL model for India where, according to their findings, fiscal deficit harms GDP. Asandului et al (2020) estimate on a sample of twelve post-communist economies and asymmetric ARDL approach that cumulative impact of fiscal policy generates inflationary output effect for countries in their sample.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%